2014
DOI: 10.3892/mmr.2014.2488
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol attenuates hypoxia/reoxygenation-induced Ca2+ overload by inhibiting the Wnt5a/Frizzled-2 pathway in rat H9c2 cells

Abstract: Abstract.Resveratrol is able to protect myocardial cells from ischemia/reperfusion-induced injury. However, the mechanism has yet to be fully elucidated. In the present study, it is reported that resveratrol has a critical role in the control of Ca 2+ overload, which is the primary underlying cause of ischemia/reperfusion injury. Hypoxia/reoxygenation (H/R) treatment decreased the cell viability and increased the apoptosis of H9c2 cells, whereas the caspase-3 and intracellular Ca 2+ levels were greatly elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…We found that RSV treatment of the SH-SY5Y neuronal cells subjected to CoCl 2 -induced HYPX modulated the structural membrane depolarization integrity and enhanced biogenesis of mitochondria and restored mitochondrial and cytosolic ROS generation functions via modulation of TRPM2. We examined whether TRPM2 channel blockers (ACA and 2-APB) mediates the effects of HYPX and RSV on mitochondria, since results of recent studies have shown that ROS generation and Ca 2+ influx via VGCC activation is important for the mitochondrial response to stress and may be linked to neuronal apoptosis and death caused by HYPX 5,8 . Consistent with present findings, the mitochondria membrane depolarization, ROS generation, apoptosis and cell via stimulation of [Ca 2+ ] i increase and TRPM2 channel activation were upregulated in the SH-SY5Y cells but not in the HEK293 cells exposed to HYPX; importantly, these were totally reversed by RSV and TRPM2 channel blocker (ACA and 2-APB) treatments.…”
Section: Discussionmentioning
confidence: 99%
“…We found that RSV treatment of the SH-SY5Y neuronal cells subjected to CoCl 2 -induced HYPX modulated the structural membrane depolarization integrity and enhanced biogenesis of mitochondria and restored mitochondrial and cytosolic ROS generation functions via modulation of TRPM2. We examined whether TRPM2 channel blockers (ACA and 2-APB) mediates the effects of HYPX and RSV on mitochondria, since results of recent studies have shown that ROS generation and Ca 2+ influx via VGCC activation is important for the mitochondrial response to stress and may be linked to neuronal apoptosis and death caused by HYPX 5,8 . Consistent with present findings, the mitochondria membrane depolarization, ROS generation, apoptosis and cell via stimulation of [Ca 2+ ] i increase and TRPM2 channel activation were upregulated in the SH-SY5Y cells but not in the HEK293 cells exposed to HYPX; importantly, these were totally reversed by RSV and TRPM2 channel blocker (ACA and 2-APB) treatments.…”
Section: Discussionmentioning
confidence: 99%
“…This study also has a few limitations. Firstly, besides the canonical Wnt/ β -catenin pathway, RSV may also regulate noncanonical Wnt pathway, such as Wnt5a [ 31 ]. Till now, at least 19 Wnt proteins were identified, forming a complex regulative network [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt5a/Ca 2+ pathway, which is a well‐known Ca 2+ ‐modulating pathway, is activated upon inflammation or ischemia/anoxia stimulation. The signaling pathway is responsible for the intracellular Ca 2+ release . Upon binding to Wnt5a, the Frizzled‐2 receptor induces Ca 2+ release from intracellular stores and activates two kinases, Ca 2+ /CaMKII and PKC, in a G‐protein dependent manner .…”
Section: Discussionmentioning
confidence: 99%